Plant Cell-Cell Transport via Plasmodesmata Is Regulated by Light and the Circadian Clock. Issue 4 (10th October 2019) - Brunkard, Jacob O.; Zambryski, Patricia
Abstract : Molecular movement through plasmodesmata, which connect plant cells to each other, is dynamically regulated by light and the circadian clock to promote intercellular transport during the day. Abstract: Plasmodesmata (PD) are essential for plant development, but little is known about their regulation. Several studies have linked PD transport to chloroplast-centered signaling networks, but the physiological significance of this connection remains unclear. Here, we show that PD transport is strongly regulated by light and the circadian clock. Light promotes PD transport during the day, but light is not sufficient to increase rates of PD transport at night, suggesting a circadian gating mechanism. Silencing expression of the core circadian clock gene, LHY/CCA1, allows light to strongly promote PD transport during subjective night, confirming that the canonical plant circadian clock controls the PD transport light response. We conclude that PD transport is dynamically regulated during the day/night cycle. Due to the many roles of PD in plant biology, this discovery has strong implications for plant development, physiology, and pathogenesis.